Assessment Of Interpersonal Activity Development In Preschool Children: A Social-Psychological Perspective (Journal of Pedagogical Inventions and Practices, 2026)
Assessment of interpersonal activity in preschool children plays an essential role in understanding their social and psychological development. Early identification of interpersonal communication skills allows educators and psychologists to support children's social competence and emotional well-being. This study investigates the assessment methods used to evaluate interpersonal activity among preschool children in educational settings. The research analyzes behavioral observation techniques, teacher assessments, and statistical evaluation of children's communication and cooperation skills. The results demonstrate that systematic assessment helps identify differences in children's interpersonal activity levels and provides valuable information for improving pedagogical practices. The findings emphasize the importance of socialpsychological assessment tools in early childhood education.